Epidemiologia e distribuição espacial da sífilis congênita em Sergipe - Silveira, Kirlly Bezerra da (2018)
Introduction: Congenital syphilis remains with a public health problem. The present study aimed to analyze the spatial distribution and its temporal trend, as well as identify risk areas for the occurrence of Congenital Syphilis and to describe characteristics associated to sociodemographic variables of mothers whose children had Congenital Syphilis in Sergipe. Methods: An ecological study, of temporal series and with techniques of spatial analysis, was performed, having the municipalities as unit of analysis. Data was obtained from Sistema de Informação de Agravos de Notificação (SINAN) and included all the new cases of Congenital Syphilis reported from 2007 to 2015 in Sergipe. Results: 2.381 new cases of congenital Syphilis were recorded in the studied period. A unique trend of incidence growth was found, ranging from 2.7 (2007) to 11 (2015) per 1000 live births. The average incidence for the period was 7,63 cases per 1000 live births. The Moran global index I = 0,64 p<0,01, indicating the existence of spatial dependence; the Moran map identified 20 municipalities as priority areas of attention in Sergipe. Most interviewed mothers - 68,46% - are between 20 and 34 years-old, 40,7% of these women have not complete middle-school and 85 % are self-declared as brown. Although, 72,7% had prenatal care, a considerable number of these women were late diagnosed, this fact reflects the fragility of the prenatal care given to these women in cited state Conclusions: There was a tendency of increasing incidence of Congenital Syphilis during the period (2007 to 2010). From 2010, the disease continued to grow; but, with a lower growth intensity when compared to previous years. From 2011 there was stabilization with an incidence remaining around 11 cases per 1000 live births by 2015. The geographical distribution of risk areas was heterogeneous, due to both territory breadth and cases concentration in certain regions. The application of different spatial analysis methods allowed to identify the priority areas of attention.